2014
DOI: 10.3892/ol.2014.2099
|View full text |Cite
|
Sign up to set email alerts
|

Primary extramedullary spinal melanoma mimicking spinal meningioma: A case report and literature review

Abstract: Primary spinal melanoma is a rare lesion, which occurs throughout the cranial and spinal regions, however, is primarily observed in the middle or lower thoracic spine. The clinical features of primary spinal melanoma are complex and unspecific, resulting in a high misdiagnosis rate. In the present case report, a rare case of spinal melanoma exhibiting the dural tail sign and mimicking spinal meningioma is reported. The initial diagnosis, using magnetic resonance imaging (MRI), was unclear. Thus, melanin-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
0
7
0
1
Order By: Relevance
“…Meningiomas císticos com localização ventricular apresentam aspectos de imagem semelhantes ao ependimoma, papiloma de plexo coroide e neurocitoma (Qiu et al 2014). Além disso, outras neoplasias podem ter características macroscópicas e de localização semelhantes (melanoma espinhal mimetizando meningioma) (Li et al 2014). Portanto, o diagnóstico definitivo é estabelecido por meio de exame histopatológico e classificação histoló-gica.…”
Section: Introductionunclassified
“…Meningiomas císticos com localização ventricular apresentam aspectos de imagem semelhantes ao ependimoma, papiloma de plexo coroide e neurocitoma (Qiu et al 2014). Além disso, outras neoplasias podem ter características macroscópicas e de localização semelhantes (melanoma espinhal mimetizando meningioma) (Li et al 2014). Portanto, o diagnóstico definitivo é estabelecido por meio de exame histopatológico e classificação histoló-gica.…”
Section: Introductionunclassified
“…PSM are located either intradurally or extradurally and may possess intra- or extramural components [ 11 ]. A review of 60 cases of PSM by Li et al [ 12 ] showed that 62.4% were extramedullary while 37.7% were intramedullary. There are also reports of multifocal primary cervical spinal cord melanomas.…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to differentiate between various melanin-containing tumors intraoperatively; however, features such as dural mater attachment and a distinct dark black color may indicate that the tumor originates from leptomeningeal melanocytes [ 12 ]. However, surgeons need to keep in mind that spinal meningiomas may mimic this appearance when complicated by hemorrhage [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of LMNs is challenging due to rarity of the disease and non‐specific imaging findings, and is complicated by the situations in which primary cutaneous melanoma may display spontaneous regression or may have been misdiagnosed as benign, or in cases where melanoma may arise from an extracutaneous site (Kanatas, Bullock, Pal, Chakrabarty, & Chumas, ; Kusters‐Vandevelde, Kusters, et al, ; Li et al, ; Wadasadawala, Trivedi, Gupta, Epari, & Jalali, ). Reports from other small case series of LMN tumors have revealed similar genomic profiling to the tumors in our study.…”
Section: Discussionmentioning
confidence: 99%